2021
DOI: 10.2217/pgs-2020-0112
|View full text |Cite
|
Sign up to set email alerts
|

Providers’ Perspectives on the Clinical Utility of Pharmacogenomic Testing in Pediatric Patients

Abstract: Aim: To assess providers’ knowledge, attitudes, perceptions, and experiences related to pharmacogenomic (PGx) testing in pediatric patients. Materials & methods: An electronic survey was sent to multidisciplinary healthcare providers at a pediatric hospital. Results: Of 261 respondents, 71.3% were slightly or not at all familiar with PGx, despite 50.2% reporting prior PGx education or training. Most providers, apart from psychiatry, perceived PGx to be at least moderately useful to inform clinical decision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…Medical liaisons from pharmacogenetic testing vendors could provide another support resource, although their expertise may not translate to medical realm. Overall, this highlights the need of providing more pharmacogenetic training and other resources for healthcare providers, which is consistent with the findings of Liko et al [49].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Medical liaisons from pharmacogenetic testing vendors could provide another support resource, although their expertise may not translate to medical realm. Overall, this highlights the need of providing more pharmacogenetic training and other resources for healthcare providers, which is consistent with the findings of Liko et al [49].…”
Section: Discussionsupporting
confidence: 91%
“…Many clinicians believe commercial pharmacogenetic testing has moderate clinical utility, despite its limitations and conflicting evidence in the literature [49]. However, these findings may be skewed in favor of pharmacogenetic testing since several of these studies were performed at sites where clinicians were already familiar with pharmacogenetics [50][51][52][53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the increase in the number of package inserts with PGx information 1 and guidelines from CPIC and DPWG, many providers are likely unaware of this information specifically and/or have limited understanding of PGx testing in general. 40,[45][46][47][48] Providers who are not aware or knowledgeable about PGx testing or have doubts about the clinical benefits of testing may have be reluctant to authorize testing or change prescriptions, which may have accounted for the muted response experienced by the pharmacists in this study. In other studies (though not in community pharmacy settings), the addition of PGx test results improved or resulted in high physician acceptance of pharmacist recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…When it contains properly integrated PGx data, an EHR should be able to support timely access to genomic information at the point of care, trigger clinical decision support mechanisms, and facilitate ordering tests and tracking their results as well as notifying patients and families [ 48 ]. A recent survey of multidisciplinary healthcare providers found that 71.3% were slightly or not at all familiar with PGx, which suggests additional education and electronic resources are needed for pediatric PGx examples [ 49 ].…”
Section: Discussionmentioning
confidence: 99%